The Role of Stakeholder Involvement in the Decision Making Process of Corporate Social Responsibility - Rosyada, Trias Amrina; Najah, Rizka Hidayatun; Amalia, Rizkyna; Kusumasari, Indah Respati; Hidayat , Rusdi (Jurnal Akuntansi, Manajemen, dan Perencanaan Kebijakan, 2024)
Stakeholder involvement is considered crucial because it can influence how effective and sustainable a company's CSR program is. Stakeholders, consisting of local communities, employees, customers and other stakeholders have diverse views on the social and environmental problems faced by the company. This research aims to see how stakeholder involvement can influence the success of a company's CSR program. This research will identify various types of stakeholders, including government, non-government organizations and local communities, and how they interact with companies to create CSR policies. The research results show that good collaboration with stakeholders not only increases transparency and accountability but also helps achieve broader social and environmental goals. To increase the positive impact of CSR initiatives, companies must actively involve stakeholders at every stage of decision making.